Male functional clinical vulnerability among institutionalized elderly - Araújo, Jeferson (2021)
Aim: To analyze functional clinical vulnerability in institutionalized elderly males in two long-term care units using the Functional Clinical Vulnerability Index (IVCF-20). Method: This is a cross-sectional and comparative study. A convenience sample was used, and as a result, 31 senior males in two institutionalized long-term institutions located in the municipality of Marabá-PA from January to May 2019 participated in the study. The IVCF-20 instrument was used to evaluate the vulnerability; a G test was applied for the statistical analysis considering a significance level of p≤0.05. All ethical requirements for research were guaranteed. Results: Among all groups, the age group between 60-74 years old, single, retired, and with a low level of education predominated. Institutionalized older people had some previous diseases such as Systemic Arterial Hypertension (50%) followed by Prostate Hyperplasia (36,8%). As for vulnerability, the groups showed an impairment in basic and instrumental activities of daily living, in cognition, in mood, mobility about reaching and / or grasping objects, aerobic and muscular capacity, gait, and urinary and fecal loss. The elderly belonging to institution A had more compromised functional clinical vulnerability than the elderly belonging to institution B. Conclusion: The results show a high degree vulnerability in institutionalized elderly citizens; discussions about public policies aimed at the elderly male population should expand.